Isyarat Bertindak sebagai Faktor Pendorong Lelaki Seks Lelaki dalam Melakukan Voluntary Counseling and Testing - Cahyo Nugroho; Tanjung Anitasari Indah Kusumaningrum (Jurnal Promosi Kesehatan Indonesia, 2018)
Background: Based on data from the Sukoharjo District AIDS Commission in 2017, MSM is the highest HIV risk group. Voluntary Counselling and Test is one of the public health strategies to do early detection and as an entry point for all HIV / AIDS health services. This study aims to describe the cause of MSM behavior on HIV test in VCT Clinic of Health center as well as in hospital in Sukoharjo.Method: This is a qualitative research using case study approach, involving five MSM that have to be interviewed deeply in terms of their behavior to routine HIV test. Two peer and outreacher also have been involved to be as triangulation informants. Informed consent was provided to the informants and signed it before interviewing them.Results: The results showed that all MSMs have ever had HIV test that were conducted by VCT mobile in their own community, but only four MSMs repeated it routinely. The MSMs who were test routinely every 3 months, have high perceived susceptibility and seriousness in terms of HIV/AIDS disease, and have higher perceived benefits and lower perceived barriers, including have many external cues to action and higher self efficacy. The underlying factor to conduct routine test was certainly peers support and high self efficacy. Therefore, this study suggested that improve self efficacy of MSM by reducing stigma and discrimination in health services and peer encouragement to MSM in doing test routinely should be important.Keywords: HIV/AIDS, Men Seks with Men, Voluntary Counselling and Test, health belief model